Flow Cytometric Measurement of Aneuploid DNA Content Correlates with High S-Phase Fraction and Poor Prognosis in Patients with Non-Small-Cell Lung Cancer. (7th August 2013) - Blanco, Rancés; Rengifo, Charles E.; Cedeño, Mercedes; Frómeta, Milagros; Rengifo, Enrique
Abstract : Cellular DNA content (ploidy) and proliferation activity (e.g., S-phase fraction) measured by flow cytometry have been usually related to the biologic aggressiveness of various neoplasms. In this study, these parameters were analyzed in paraffin-embedded tumor specimens from 43 cases of resected non-small-cell lung cancer (NSCLC). Additionally, the correlation of them with both prognosis and a variety of clinic-pathological features were investigated. The stage and the appearance of both local recurrence and metastasis were related to overall survival of patients. Twenty-two tumors (51.2%) had a diploid DNA distribution, while 21 were aneuploid (48.8%). The mean of aneuploidy was 1.6% ± 0.3%. A correlation was found between ploidy and survival as well as with the appearance of local recurrence and/or metastasis. The mean values of S-phase fraction of diploid and aneuploid tumors were 16.7 ± 11.3% and 32.9 ± 12.1%, respectively, which were significantly different (P = 0.0022 ). Similar results were obtained analyzing the proliferation index (sum of cells in S and G2 /M phases of cell cycle) (P = 0.0040 ). However, no correlation between these parameters and both overall survival of patients and clinicopathological features was observed. Our results could suggest the potential use of ploidy analysis as a useful complement of TNM stage in NSCLC.